Assessing the Challenges and Coping Strategies Adopted by Street Children of School Going Age in the Tamale Metropolis: Policy Implications - Mohammed Gunu, Ibrahim Mohammed; Siibaway, Mohammed; Sulemana Achanso , Adams; Sulemana Achanso , Adams (Advances in Social Sciences Research Journal, 2021)
Children form the foundation of every society. They are expected to be trained, supported and guided to become responsible to the society. In Ghana, the 1992 constitution (Article 28, clause 1), the children’s Act (Act 560) and the Child Rights Regulations 2002 (LI.1705) are among the measures put in place to promote the wellbeing of children in the country. However, there are significant numbers of children who are living in many city streets in Ghana including the Tamale metropolis. These street children are living the life that has the tendency to affect their physical and mental development. This paper examines the challenges street children in Tamale face and their coping strategies. It also explores various policy options to ensure their continuous education. The study used a case study design to collect both qualitative and quantitative data. Findings of the research show that street children encounter challenges related to accommodation, education, sexual abuse, health, security, and malnourishment and in some cases death. The paper also found that street children adopt variety of strategies including relying on self-medication, hawking and the formation of networks to cope with the various challenges they encounter on the street. However, the education of these children is a big challenge. It is in the light of this, that the paper calls on relevant key stakeholders to put in serious efforts towards tackling the education of street children and child streetism in the Tamale metropolis to ensure access and quality of education of these children.